PEDAGOGICAL FACTORS AFFECTING THE PHYSICAL DEVELOPMENT OF PRIMARY SCHOOL CHILDREN (American Journal of Pedagogical and Educational Research, 2023)
The model of physical education of schoolchildren is considered as a set of forms of physical education united for one purpose and aimed at solving health and educational-pedagogical tasks.